2006
DOI: 10.1093/pcp/pcj012
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of cDNAs for R2R3-MYB, bHLH and WDR Transcriptional Regulators and Identification of c and ca Mutations Conferring White Flowers in the Japanese Morning Glory

Abstract: The transcriptional regulators for anthocyanin biosynthesis include members of proteins containing an R2R3-MYB domain, a bHLH (basic helix-loop-helix) domain and conserved WD40 repeats (WDRs). Spacial and temporal expression of the structural genes encoding the enzymes for anthocyanin biosynthesis is thought to be determined by combinations of the R2R3-MYB, bHLH and WDR factors and their interactions. While the wild-type Japanese morning glory (Ipomoea nil) exhibits blue flowers with colored stems and dark-bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
205
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(217 citation statements)
references
References 60 publications
9
205
0
3
Order By: Relevance
“…In Antirrhinum majus and tobacco, AmMYB305 (or its orthologue in tobacco) activated the gene encoding the first enzyme of phenylpropanoid metabolism, phenylalanine ammonia lyase (PAL) (Urao et al 1993). Morita et al (2006) reported that spatial and temporal expression of the structural genes encoding the enzymes for anthocyanin biosynthesis was determined by combinations of the R2R3-MYB, bHLH and WDR factors and their interaction. Lin- Wang et al (2010) described the association of MYBA or MYB1 and MYB10 with regulation of the anthocyanin biosynthetic pathway in Rosaceae.…”
Section: Phenylpropanoid Metabolismmentioning
confidence: 99%
“…In Antirrhinum majus and tobacco, AmMYB305 (or its orthologue in tobacco) activated the gene encoding the first enzyme of phenylpropanoid metabolism, phenylalanine ammonia lyase (PAL) (Urao et al 1993). Morita et al (2006) reported that spatial and temporal expression of the structural genes encoding the enzymes for anthocyanin biosynthesis was determined by combinations of the R2R3-MYB, bHLH and WDR factors and their interaction. Lin- Wang et al (2010) described the association of MYBA or MYB1 and MYB10 with regulation of the anthocyanin biosynthetic pathway in Rosaceae.…”
Section: Phenylpropanoid Metabolismmentioning
confidence: 99%
“…For example, mutations in the structural genes CHS (for chalcone synthase), DFR (for dihydroflavonol 4-reductase), and ANS (for anthocyanidin synthase) involved in anthocyanin biosynthesis cause flower color changes (Stracke et al, 2009;Tanaka et al, 2009;Vanholme et al, 2010). Genetic mutations causing color changes of plant organs also occur in genes regulating anthocyanin biosynthesis, such as transcription factors (Boss et al, 1996;Morita et al, 2006;Park et al, 2007;Allan et al, 2008;Chiu et al, 2010). The transcription factors involved in anthocyanin biosynthesis include R2R3-MYB, bHLH (for basic helix-loop-helix), and WDR (for WD-repeat protein), which regulate the downstream structural genes by forming the MYBbHLH-WD40 complex, which is involved in the anthocyanin biosynthesis pathway (Holton and Cornish, 1995;Winkel-Shirley, 2001;Schwinn et al, 2006;Gonzalez et al, 2008).…”
mentioning
confidence: 99%
“…The transcription factors involved in anthocyanin biosynthesis include R2R3-MYB, bHLH (for basic helix-loop-helix), and WDR (for WD-repeat protein), which regulate the downstream structural genes by forming the MYBbHLH-WD40 complex, which is involved in the anthocyanin biosynthesis pathway (Holton and Cornish, 1995;Winkel-Shirley, 2001;Schwinn et al, 2006;Gonzalez et al, 2008). Mutations including nucleotide substitutions, deletions, and insertions in the MYB gene result in color changes in plant organs (Boss et al, 1996;Morita et al, 2006). Transposon insertions in the bHLH gene cause white flowers in common morning glory (Ipomoea purpurea; Park et al, 2007), whereas simultaneous mutations of a nucleotide deletion in MYB and a nucleotide insertion in WDR change morning glory flower color from blue to white (Chiu et al, 2010).…”
mentioning
confidence: 99%
“…Regulatory genes have been also characterized in several ornamental plant species, including Japanese morning glory (Morita et al 2006), gerbera (Elomaa et al 1998;Elomaa et al 2003), torenia (Nishijima et al 2013), Mimulus aurantiacus (Streisfeld et al 2013), and peach (Uematsu et al 2014). Several reports have appeared on the regulation of floral anthocyanin pigmentation in non-ornamental plants, such as soybean (Takahashi et al 2013), kiwifruit (Fraser et al 2013), and tobacco (Pattanaik et al 2010).…”
Section: Transcription Factors Responsible For Anthocyanin Biosynthesmentioning
confidence: 99%